2008
DOI: 10.1098/rspb.2008.0870
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation in brown trout early life-history traits: implications for climate change adaptability

Abstract: Knowledge of local adaptation and adaptive potential of natural populations is becoming increasingly relevant due to anthropogenic changes in the environment, such as climate change. The concern is that populations will be negatively affected by increasing temperatures without the capacity to adapt. Temperature-related adaptability in traits related to phenology and early life history are expected to be particularly important in salmonid fishes. We focused on the latter and investigated whether four population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
218
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(234 citation statements)
references
References 62 publications
10
218
4
2
Order By: Relevance
“…Coupled with this variability was the observation that quantitative trait differentiation (Q ST ) exceeded neutral molecular differentiation (F ST ) for body length at two different developmental stages (alevin, swim-up). As documented by Haugen and Vllestad (2000) for grayling, Jensen et al (2008) found evidence of genetic variability in plasticity among individuals within populations, as indicated by significant sire  temperature interactions. They further supported their conclusion that population differences in reaction norms were a consequence of natural selection by arguing for potentially adaptive responses by alevin length and growth rate to temperatures that the populations were most likely to experience in the wild.…”
Section: Differences Among Populationsmentioning
confidence: 92%
“…Coupled with this variability was the observation that quantitative trait differentiation (Q ST ) exceeded neutral molecular differentiation (F ST ) for body length at two different developmental stages (alevin, swim-up). As documented by Haugen and Vllestad (2000) for grayling, Jensen et al (2008) found evidence of genetic variability in plasticity among individuals within populations, as indicated by significant sire  temperature interactions. They further supported their conclusion that population differences in reaction norms were a consequence of natural selection by arguing for potentially adaptive responses by alevin length and growth rate to temperatures that the populations were most likely to experience in the wild.…”
Section: Differences Among Populationsmentioning
confidence: 92%
“…Factors such as temperature may vary considerably among and within rivers at smaller geographical scales and may represent potent selection regimes (Jensen et al, 2008). However, information at this geographical scale was not available for all sampled localities.…”
Section: Landscape Genomicsmentioning
confidence: 99%
“…Recently, the development of statistical and conceptual frameworks such as the Q ST -F ST approach (Merilä and Crnokrak, 2001) has enabled more rigorous testing of selection and local adaptation at the phenotypic level among salmonid populations (Koskinen et al, 2002;Perry et al, 2005;Jensen et al, 2008). Moreover, the revolutionizing developments in the genomic sciences have led to the generation of vast amounts of molecular resources available in silico, which can readily be used for identification of suitable genetic markers (Bouck and Vision, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In ecological systems, short-term adaptive strategies usually refer to acclimation to a new (or temporary) environmental state; acclimation may draw on phenotypic plasticity, habitat diversity, or short-term behavioral responses (Stillman 2003). If an environmental stressor or shift continues, long-term adaptive strategies depend on evolutionary responses at the species level or migration strategies (leaving the area for better suited habitats; Jensen et al 2008, Chown et al 2010, Ekstrom et al 2015. Social communities may cope with change in the short term through social networks, informal arrangements, alternative income generating activities, or financial remittances from overseas family members (Adger 2003, Adger et al 2007).…”
Section: Temporal Scale and Orientationmentioning
confidence: 99%